Water–rock two-phase flow model for water inrush and instability of fault rocks during mine tunnelling - Dan Ma; Hongyu Duan; Qiang Li; Jiangyu Wu; Wen Zhong; Zhen Huang (International Journal of Coal Science & Technology, 2023)
Abstract Water inrush hazard is one of the major threats in mining tunnel construction. Rock particle migration in the seepage process is the main cause of water inrush pathway and rock instability. In this paper, a radial water–rock mixture flow model is established to study the evolution laws of water inrush and rock instability. The reliability of the proposed model is verified by the experimental data from a previous study. Through the mixture flow model, temporal-spatial evolution laws of different hydraulic and mechanical properties are analysed. And the proposed model’s applicability and limitations are discussed by comparing it with the existing water inrush model. The result shows that this model has high accuracy both in temporal evolution and spatial distribution. The accuracy of the model is related to the fluctuation caused by particle migration and the deviation of the set value. During the seepage, the porosity, permeability, volume discharge rate and volume concentration of the fluidized particle increase rapidly due to the particle migration, and this phenomenon is significant near the fluid outlet. As the seepage progresses, the volume concentration at the outlet decreases rapidly after reaching the peak, which leads to a decrease in the growth rate of permeability and porosity, and finally a stable seepage state can be maintained. In addition, the pore pressure is not fixed during radial particle migration and decreases with particle migration. Under the effect of particle migration, the downward radial displacement and decrease in effective radial stress are observed. In addition, both cohesion and shear stress of the rock material decreased, and the rock instability eventually occurred at the outlet.